Організаційні аспекти формування комплекту машин будівельного підприємства в рамках девелоперського конктакту - Шаляпіна, Т. С. (Ways to Improve Construction Efficiency, 2014)
We consider the organizational aspects of the formation of a set of construction machinery based on a systematic approach and the method of rational choice.